1998
DOI: 10.1034/j.1600-0501.1998.090502.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic evaluation, following delivery of fixed reconstructions, at GBR treated titanium fixtures

Abstract: Conditions following incorporation of fixed reconstructions, at endosseous titanium implants augmented at local bony dehiscence and fenestration defects using a bioabsorbable Resolut membrane were studied in 7 patients. Fixture stability, radiographic marginal bone levels and peri-implant soft tissue status were evaluated at 21 membrane treated and 17 control fixtures (installed in regions of adequate bone volume), following a 2-year period of functional loading. Prosthetic reconstructions were removed and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
73
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 0 publications
14
73
0
1
Order By: Relevance
“…In the current study, no significant differences were observed between the two groups for the amount of marginal bone loss after 1 year of implant installation. These data are in agreement with studies evaluating implants placed in native and regenerated bone 24‐26 . Mayfield et al 24 in 1998 reported a mean marginal bone loss of 0.6 mm for control and 0.7 mm for the test implants over a period of 23 to 27 months after the prosthesis installation.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the current study, no significant differences were observed between the two groups for the amount of marginal bone loss after 1 year of implant installation. These data are in agreement with studies evaluating implants placed in native and regenerated bone 24‐26 . Mayfield et al 24 in 1998 reported a mean marginal bone loss of 0.6 mm for control and 0.7 mm for the test implants over a period of 23 to 27 months after the prosthesis installation.…”
Section: Discussionsupporting
confidence: 85%
“…These data are in agreement with studies evaluating implants placed in native and regenerated bone 24‐26 . Mayfield et al 24 in 1998 reported a mean marginal bone loss of 0.6 mm for control and 0.7 mm for the test implants over a period of 23 to 27 months after the prosthesis installation. However, in these studies, 24‐26 guided bone regeneration was performed simultaneously with implant installation to treat bone dehiscence and fenestration defects.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A second study providing controls reported on 38 implants in seven patients (Mayfield et al 1998). Twenty‐one of these implants were placed in conjunction with GBR, whereas 17 could be placed into the host bone without regenerative therapy.…”
Section: Resultsmentioning
confidence: 99%
“…In five studies, 2‐year data accounting for 656 implants treated with GBR were reported (Dahlin et al 1991b, Mayfield et al 1998, Nevins et al 1998, Lorenzoni et al 1999, Brunel et al 2001). Of these implants 526, all reported in one study (Nevins et al 1998), yielded a survival rate of 97.5%, whereas the other 130 implants, reported in four studies (Dahlin et al 1991b, Mayfield et al 1998, Lorenzoni et al 1999, Brunel et al 2001), showed 100% survival over the 2‐year observation period.…”
Section: Resultsmentioning
confidence: 99%